Radikalisme, Liberalisme dan Terorisme: Pengaruhnya Terhadap Agama Islam - Yunus, A Faiz (Jurnal Studi Al-Qur’an, 2017)
Focuses this study is the issues of radicalism, liberalism and terrorism . The world today more famaous with issues of extremism, fondametalism and radicalism. Crime or violence is a phenomenon that we often hear and see, both in mass media and in reality around our environment and society. The latest news and a warm discussion, audiences and mass media and electronics is terrorism. Terrorism is always synonymous with terror, violence, extremism and intimidation, which often leads to negative consequences of casualties. The research entitled "Radicalism, Liberalism And Terrorism: Its Influence to Islam" examines the phenomena occurring in the world both in general and from issues of extremism, fondametalism and religious radicalism. This Researchers review descriptive method is a method in researching the setatus of human groups, conditions, systems of thought, or phenomenon at this time. With the aim of making a systematic, factual and accurate description of the facts, traits and relationships among the phenomena under investigation Keywords: Radicalism, Liberalism, Terrorism, Religious, Abstrak Penelitian ini lebih fokus kepada isu-isu radikalisme, liberalism dan terorisme yang berkembang akhir-akhir ini. Dunia sedang digoncang dengan isu-isu ekstremisme, fondametalisme dan radikalisme. Kejahatan atau kekerasan adalah suatu fenomena yang sering kita dengar dan lihat, baik di media massa maupun realitas yang ada di sekitar lingkungan dan masyarakat kita. Kabar terbaru dan yang hangat dibicarakan, khalayak serta media massa dan elektronik yaitu terorisme. Terorisme selalu identik dengan teror, kekerasan, ekstrimnitas dan intimidasi sehingga seringkali menimbulkan konsekuensi negatif menjatuhkan korban yang banyak. Penelitian yang berjudul â€œRadikalisme, Liberalisme Dan Terorisme: Pengaruhnya Terhadap Agama Islamâ€ ini mengkaji tentang fenomina yang terjadi di dunia baik secara umum maupun dari isu-isu ekstremisme, fondametalisme dan radikalisme agama. Jenis penelitian ini adalah kualitatif deskriptif yang merupakan suatu metode dalam meneliti setatus kelompok manusia, kondisi, sistem pemikiran, ataupun fenomina pada saat ini. Kata Kunci: Radikalisme, Liberalisme, Terorisme Agama